Biodegradable liposome-encapsulated hydrogels for biomedical applications: a marriage of convenience - Grijalvo, Santiago; Mayr, Judith; Eritja, Ramon; Díaz, David Díaz (Biomaterials science, 2016)
Hydrogels are hydrophilic three-dimensional networks with demonstrated potential for medical and pharmaceutical applications. Specifically, biopolymer-based hydrogels offer certain advantages over synthetic polymers in terms of biocompatibility and biodegradability. Because of their inherent properties, hydrogels are able to efficiently encapsulate and liberate in a controlled release manner, different hydrophobic and hydrophilic therapeutic molecules, including nucleic acids, proteins and antibodies. Several strategies have been reported in the literature to minimize the potential burst release of encapsulated drugs, thus preventing their local accumulation and consequent toxic responses. Within this context, liposomes embedded in hydrogels have emerged as an attractive strategy to reduce this undesirable effect. This tutorial review covers a selection of the most promising cationic, neutral and anionic biopolymer-based hydrogels containing liposomes, niosomes or vesicles for drug delivery or tissue engineering applications. Liposome-encapsulated hydrogels have emerged as an attractive strategy for medical and pharmaceutical applications.